Connecting Higher Education to the Labour Market: The Experience of Service Learning in a Portuguese University - Sofia Castanheira Pais; Teresa Silva Dias; Deyse Benício (Education Sciences, 2022)
The mission of higher education institutions (HEI) includes fostering conditions that enable student participation, and a commitment to their professional success. Pedagogical strategies which combine learning that goes beyond the university and involves a service-learning (SL) course carried out in the context of a pedagogical innovation programme of the University of Porto were examined. This examination included interviews with teachers, a focus group discussion with students and the analysis of logbooks and final reports to realize the potential of SL for improving employability. The results put into perspective the weaknesses and potentialities of SL courses at HEI and show that when academic learning is integrated with community experience, students gain both personal/social and academic skills. They also develop leadership and communication skills and critical awareness on the one hand and time and resources management and the ability to adapt and respond to challenges of the real world on the other, all seen as beneficial for the transition into the labour market.